Inhibition of DNA binding of purified p55v-myc in vitro by antibodies against bacterially expressed myc protein and a synthetic peptide. - Bunte, T (1984)
To identify viral myc proteins, we have prepared myc-specific antibodies: (i) against a synthetic peptide corresponding to the nine carboxy-terminal amino acids of the viral myc (C9); (ii) against a bacterially expressed viral myc protein obtained by inserting the SalI-BamHI fragment of the viral MC29 DNA clone in the expression vector pPLc24. Both antisera recognize a protein of 55 000 mol. wt., p55v-myc, in MH2- and OK10-transformed fibroblasts. The protein is located in the nucleus, as shown by indirect immunofluorescence and cell fractionation. Antibodies against the C9 peptide were used to purify the p55v-myc by immunoaffinity column purification (3000-fold) from OK10- and MH2-transformed fibroblasts. p55v-myc binds to double-stranded DNA in vitro as does p110gag-myc. DNA binding in vitro is inhibited by the immunoglobulin fraction of antibodies against the bacterially expressed myc protein. Furthermore, a synthetic peptide consisting of 16 amino acids (C16) was used to isolate specific immunoglobulins which also inhibit DNA binding in vitro. OK10 codes, in addition to p55v-myc, for a p200gag-pol-myc polyprotein. The majority of this protein is located in the cytoplasm (79%). The purified protein binds to single-stranded RNA in vitro, unlike other gag-myc or myc proteins.